Internal Structure of the Mantle Transition Zone Beneath the Contiguous U.S.: Insights From the 520‐km Discontinuity Revealed by Ambient Noise Correlations - Y. A. Aiman; Y. Lu; C. Esteve; G. Bokelmann (Geophysical Research Letters)
Abstract We investigate the internal structure of the Mantle Transition Zone (MTZ) beneath the contiguous U.S. by mapping the depth of the 520‐km discontinuity (d520) and the relative amplitude of seismic phases associated with the 520‐, 410‐, and 660‐km discontinuities. Specifically, we analyze short‐period reflected waves between 3 and 10 s from the MTZ discontinuities extracted from seismic noise correlations. Our results show lateral d520 depth variations, deeper in the western U.S., likely indicating a warmer upper MTZ. Analysis of relative phase amplitude between the MTZ interfaces highlights a strong d520 reflection phase across the central U.S., supporting previous studies that report high seismic velocity contrasts and elevated olivine content. In contrast, the eastern U.S. shows a weaker d520 reflection phase, which may be attributed to a gradual seismic velocity transition and lower water content. The MTZ composition also likely varies across the U.S., with potential basalt accumulation in the southwest due to past subduction events.